Properties of the Thiamine Transport System in Escherichia coli - Yamada, Kazuo (1980)
Thiamine transport was studied with a mutant (KG1976) of Escherichia coli K-12 deficient in thiamine kinase (EC 2.7.1.89), which catalyzes the formation of thiamine monophosphate from thiamine. Mutant cells accumulated thiamine 390-fold as the free form against a concentration gradient in the absence of added carbon sources at the steady state. Thiamine taken up from the medium, or thiamine preloaded in the absence of glucose, was expelled into the medium when glucose, d-lactate, or succinate was added, whereas exit in the absence of glucose was very slow. The rate of thiamine entry was therefore determined in the absence of glucose, and that of thiamine exit was followed by the addition of glucose to thiamine-preloaded cells. The activities of thiamine entry and exit were optimal at 42 and 37°C, respectively. Hyperbolic saturation kinetics were obtained for the entry rate with a K(m) value of 5.9 nM. The exit rate showed a sigmoidal dependence on cellular thiamine concentrations, and a half-maximal velocity was observed at 31 μM. The rates of both entry and exit were lowered by electron transport inhibitors and uncouplers, suggesting that the energy coupled to both processes was provided through substrate oxidation. Thiamine exit from K(+)-depleted cells was enhanced by K(+) alone and by Na(+) to a much lesser extent, and K(+) and glucose were found to be synergistic for thiamine exit. These cations had no effect on the entry of thiamine into KG1676 cells in the absence of glucose. These properties of the entry and exit of thiamine in KG1676 are discussed from the standpoint of the possible involvement of different membrane components or different sites of identical thiamine carrier protein.